Intergenerational Support and the Emotional Well‐being of Older Jews and Arabs in Israel. Issue 4 (1st July 2013) - Silverstein, Merril; Lowenstein, Ariela; Katz, Ruth; Gans, Daphna; Fan, Yu‐Kang; Oyama, Petrice
Abstract : This investigation examined the cultural context of intergenerational support among older Jewish and Arab parents living in Israel. The authors hypothesized that support from adult children would be more positively consequential for the psychological well‐being of Arab parents than of Jewish parents. The data derived from 375 adults age 65 and older living in Israel. Psychological well‐being was measured with positive and negative affect subscales of the Positive and Negative Affect Schedule. Overall, positive affect was highest when filial expectations for support were congruent with whether or not instrumental support was received. Findings by cultural background revealed that, among older Jews, receiving instrumental support raised positive affect and stronger filial expectations lowered it. Among older Arabs, receiving financial support raised positive affect and receiving instrumental support lowered it. Culture appears to serve as a potent force in determining which types of intergenerational support functions are expected and accepted means of serving the everyday needs of older parents .